Characterization of the complete mitochondrial genome sequence of Ujumuqin sheep (Ovis aries). (4th May 2017) - Yang, Cuiting; Li, Li; Zhong, Tao; Wang, Linjie; Zhang, Hongping
Abstract: Sheep is one of the most important and widespread domestic animals. Nevertheless, the origins of most sheep breeds are poorly understood, specifically the fat-tailed sheep that maternally originates from a specific group. Here, we reported the whole mitochondrial DNA of Ujumuqin sheep ( Ovis aries ), derived from one of the oldest fat-tailed sheep breed-Mongolian sheep in China. It harbors 2 ribosomal RNA genes, 13 protein-coding genes, 22 transfer RNA genes, and a D-Loop region. The mitogenome is 16 617 bp in length, with a homology of 50% between the mitogenome of Ujumuqin sheep and that of Texel sheep. The unveiling of the mitochondrial DNA sequence of Ujumuqin sheep will have a significant role to play in the further studies on sheep evolution and domestication.